2011
DOI: 10.2166/wst.2011.370
|View full text |Cite
|
Sign up to set email alerts
|

Autotrophic nitrogen removal at low temperature

Abstract: In this work the autotrophic nitrogen removal was carried out at moderately low temperatures using two configurations: a) two-units one comprising a SHARON reactor coupled to an Anammox SBR and b) single-unit one consisting of a granular SBR performing the CANON process. At 20°C the two-units system was limited by the Anammox step and its nitrogen removal capacity was around ten times lower than the CANON system (0.08 g N/(L d) versus 1 g N/(L d)). When the CANON system was operated at 15°C the average removed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(43 citation statements)
references
References 16 publications
4
38
0
1
Order By: Relevance
“…Both sequential processes can be performed in a "two-units" configuration, where the partial nitrification and Anammox processes take place in separated units, or in a "single-unit" configuration, where both types of microorganisms (AOB and Anammox) coexist in the same unit. Vazquez-Padín et al [23] compared both types of configurations operated at moderate temperatures and observed that the "two-units" system efficiency was limited by the Anammox step. In this case the achieved nitrogen removal capacity was around ten times lower than the "single-unit" system.…”
Section: Anammox Processmentioning
confidence: 99%
“…Both sequential processes can be performed in a "two-units" configuration, where the partial nitrification and Anammox processes take place in separated units, or in a "single-unit" configuration, where both types of microorganisms (AOB and Anammox) coexist in the same unit. Vazquez-Padín et al [23] compared both types of configurations operated at moderate temperatures and observed that the "two-units" system efficiency was limited by the Anammox step. In this case the achieved nitrogen removal capacity was around ten times lower than the "single-unit" system.…”
Section: Anammox Processmentioning
confidence: 99%
“…Thus, for areas in which the water temperature is generally below 25°C, it would be difficult to achieve field applications because artificial heating leads to relatively higher costs. Several researchers successfully operated anammox process under moderate and low temperature, but, the nitrogen removal rates (NRRs) of the reactors are consistently below 1.0 kg N m À3 d À1 when the environmental temperature is below 20°C (Isaka et al, 2007;Vázquez-Pádin et al, 2011;Hendrickx et al, 2012;Lotti et al, 2014). Hence, a better reactor capacity under low temperature is in need and auxiliary enhancement method should be implemented.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it was reported that the activities of anammox bacteria and AOB both decreased at 15 to 20°C (13, 14) and that partial nitrification was difficult to achieve in winter because of the varying temperature of municipal wastewater (15). Nevertheless, several studies showed that nitrogen removal at a lower temperature by an anammox process can work (14,16,17); still, in none of these studies was it possible to maintain a stable anammox-AOB culture (nitritation-anammox) at temperatures lower than 20°C. On the other hand, in natural ecosystems, such as Northern European soils and marine sediments, anammox bacteria thrive under much colder temperatures and very low ammonium concentrations (M range) (18,19).…”
mentioning
confidence: 99%